Junie B. Jones has a peep in her pocket - Park, Barbara; Brunkus, Denise (New York : Scholastic, 2000)
When Junie B. learns that her kindergarten class is going on a field trip to a farm, she worries about being attacked by a rooster.
L
"A Stepping Stone book."
b
b
Keywords: School field trips -- Fiction; Farms -- Fiction; Fear -- Fiction